Redesign Of al-rahma medical clinic - honjol, Ala’; kharoub, Amal; qabaha, Liana (My University, 2018)
A medical clinic is a health care facility that is primarily focused on the care of outpatients. Clinics can be privately or publicly managed. They typically cover the primary health-care needs of populations in local communities, in contrast to larger hospitals which offer specialized treatments and admit inpatients for overnight stays. Including this project the Medical Clinic includes internal facilities that mainly host health-care for people with injuries or illnesses to come and be seen by a triage nurse or other health workers, these facilities essentially include, reception and waiting hall, general surgery room, Examination rooms, X-rays and labs rooms, emergency room, Management room, Accounting and financial room, pharmacy. Furthermore, outside spaces such as a parking for Car workers and ambulances. The main objective of this project is to redesign Al- rahma medical clinic structurally safe and environmentally comfortable. during semester graduation project 1 have analyzed and identified the problems facing Al-rahma medical clinic,then during semester graduation project 2 have been tried to improve all the problems and find solutions for them. all of architecture, structural , mechanical , electrical and HVAC plans has been designed and performed. Then to analyze architecture design, structure design, lighting design , HVAC system design there are some programs and codes that has been used in this study, These programs are Rivet for 3-D models and Auto-CAD for 2-D plans to design architectural, ETABS and SAP 2000 to design Structural element, Design Builder program to design solar and HVAC system with ASHRE standard for heating, ventilation and air conditioning have been used used, INSUL program has been use for Acoustic ,In addition to DIAlux program has been used for lighting design depending on LEED specification . And the codes that will be used like Uniform building Code (UBC-97), International Building Code (IBC), Jordanian Building Code 2005, Arab Uniform Code 2006 and ACI 318(2011). The results and outcomes were introduced in the form of a report with attached tender documents. These documents include design details, tables of quantities and shop drawings.